2010
DOI: 10.1111/j.1756-1051.2009.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabia's tallest trees: ecology, distribution and conservation status of the regionally endangered tree speciesMimusops laurifolia

Abstract: Mimusops laurifolia (Forssk.) Friis is the largest tree species in the Arabian Peninsula, and a characteristic species of the threatened southwest Arabian valley forest habitat. In order to understand the distribution and conservation status of M. laurifolia, this paper collates the historical records of M. laurifolia and compares them with recent survey data. This comparison highlights that the abundance of M. laurifolia has dramatically declined at sites that were previously considered important for this spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Causes for sparse vegetation coverage and limited plant diversity of the area could be due to many interrelated factors like: high moisture stress, human interference, recurrent drought, soil erosion, overgrazing, limited efforts toward conservation and rehabilitation. Extensive human interferences and climate changes and subsequent deterioration and continuous decline of many tree species and forest habitats have been reported for the region ( Batanouny, 1991 , Hall, 2005 , El-Juhany, 2009 , Hall et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Causes for sparse vegetation coverage and limited plant diversity of the area could be due to many interrelated factors like: high moisture stress, human interference, recurrent drought, soil erosion, overgrazing, limited efforts toward conservation and rehabilitation. Extensive human interferences and climate changes and subsequent deterioration and continuous decline of many tree species and forest habitats have been reported for the region ( Batanouny, 1991 , Hall, 2005 , El-Juhany, 2009 , Hall et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Al-Ghamdi (2007) , nearly 70% of the beekeeping production in the country is concentrated in this region, where these plant types play the major role as honey bee flora. However, Hall et al (2010) reported the apicultural landscapes (forests) are under various degrees and types of degradation, deteroriations and continuous declining of tree species. Moreover in the region, the presence of die-back and poor regeneration of trees and extensive declining of woodlands were reported ( El-Juhany, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover in the region, the presence of die-back and poor regeneration of trees and extensive declining of woodlands were reported ( El-Juhany, 2009 ). Furthermore, Hall et al (2010) reported that the remaining patches of relict forest habitats are under continuous declining both in quality and quantity and some tree species become endangered with only little or no regeneration. Hence, worth to think of restoration of degraded apicultural landscapes before conditions are worsened.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ethno-botanical research would also be of value to understand the socio-economic importance of this species. These complementary lines of research are needed to develop and reinvigorate a traditional conservation system in which D. ombet would be featured as a flagship species to promote biodiversity conservation and sustainable use in the threatened areas where the Nubian dragon tree is found (Hall et al, 2010).…”
Section: Discussionmentioning
confidence: 99%